The Gronnedal-Ika Carbonatite-Syenite Complex, South Greenland: Carbonatite Formation by Liquid Immiscibility - HALAMA, RALF; VENNEMANN, TORSTEN; SIEBEL, WOLFGANG; MARKL, GREGOR (Journal of Petrology, 2005)
The Grønnedal-Ika complex is dominated by layered nepheline syenites which were intruded by a xenolithic syenite and a central plug of calcite to calcite–siderite carbonatite. Aegirine–augite, alkali feldspar and nepheline are the major mineral phases in the syenites, along with rare calcite. Temperatures of 680–910°C and silica activities of 0·28–0·43 were determined for the crystallization of the syenites on the basis of mineral equilibria. Oxygen fugacities, estimated using titanomagnetite compositions, were between 2 and 5 log units above the fayalite–magnetite–quartz buffer during the magmatic stage. Chondrite-normalized REE patterns of magmatic calcite in both carbonatites and syenites are characterized by REE enrichment (La CN –Yb CN = 10–70). Calcite from the carbonatites has higher Ba (∼5490 ppm) and lower HREE concentrations than calcite from the syenites (54–106 ppm Ba). This is consistent with the behavior of these elements during separation of immiscible silicate–carbonate liquid pairs. ε Nd (T = 1·30 Ga) values of clinopyroxenes from the syenites vary between +1·8 and +2·8, and ε Nd (T) values of whole-rock carbonatites range from +2·4 to +2·8. Calcite from the carbonatites has δ18O values of 7·8 to 8·6‰ and δ13C values of −3·9 to −4·6‰. δ18O values of clinopyroxene separates from the nepheline syenites range between 4·2 and 4·9‰. The average oxygen isotopic composition of the nepheline syenitic melt was calculated based on known rock–water and mineral–water isotope fractionation to be 5·7 ± 0·4‰. Nd and C–O isotope compositions are typical for mantle-derived rocks and do not indicate significant crustal assimilation for either syenite or carbonatite magmas. The difference in δ18O between calculated syenitic melts and carbonatites, and the overlap in ε Nd values between carbonatites and syenites, are consistent with derivation of the carbonatites from the syenites via liquid immiscibility.